(CoxMg1−x)O nanocondensates by pulsed laser ablation of bulk alloy in air1. Issue 26 (14th July 2015) - Chen, Bang-Ying; Lin, Shih-Siang; Shen, Pouyan; Chen, Shuei-Yuan
<x xml:space="preserve">Abstract</x> (Co, Mg)O nanocondensates produced by pulsed laser ablation of MgO–CoO solid solution target in air.